2005
DOI: 10.1186/1476-4598-4-25
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming cisplatin resistance by mTOR inhibitor in lung cancer

Abstract: Background: Cisplatin resistance is complex and involves several different mechanisms. Employing cDNA microarray analysis, we have found that cisplatin resistant cells share the common characteristic of increase in ribosomal proteins and elongation factors. We hypothesize that in order to survive cisplatin treatment, cells have to synthesize DNA repair proteins, antiapoptotic proteins and growth-stimulating proteins. Thus, by blocking the translation of these proteins, one should be able to restore cisplatin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 35 publications
(25 reference statements)
1
39
0
2
Order By: Relevance
“…CCI-779 also has substantial single-agent activity in certain haematologic malignancies such as mantle cell lymphoma [91]. In addition, rapamycin and rapalogues have demonstrated efficacy in combination with other chemotherapeutics [9294]. …”
Section: Therapeutic Targeting Of Cap-dependent Translational Complexmentioning
confidence: 99%
“…CCI-779 also has substantial single-agent activity in certain haematologic malignancies such as mantle cell lymphoma [91]. In addition, rapamycin and rapalogues have demonstrated efficacy in combination with other chemotherapeutics [9294]. …”
Section: Therapeutic Targeting Of Cap-dependent Translational Complexmentioning
confidence: 99%
“…mTOR inhibitors have shown their efficacy in enhancing the effects of chemotherapeutics agents in various malignancies (25–29). We have recently demonstrated that the mTOR inhibitor, rapamycin, potentiates the anti-proliferative effects of paclitaxel in endometrial cancer cell lines (30).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that mTOR1-S6K1 signaling controls the transcription of FANCD2 [42, 43]. In this regard, we have previously shown that arginine deprivation by ADI-PEG20 leads to inhibition of mTOR [5] while cisplatin treatment can result in mTOR activation [9, 44]in an attempt to evade cell death. Thus, it is possible that inhibition of mTOR by arginine deprivation is a possible mechanism(s) why FANCD2 is decreased.…”
Section: Discussionmentioning
confidence: 99%